Brand promotion through online advertising: current tools - K. A. Arzhanova; A. I. Eremeeva (Цифровая социология, 2024)
In the conducted research, the authors describe the features of brand promotion using Internet marketing tools. The key types of online advertising and their differences are given alongside with the data on the Internet advertising market and its specifics. The purpose of the study was to determine the features of brand promotion with the help of online advertising. To achieve it, the following objectives were set: to consider the available types of online advertising; to analyse the cases of 5 Russian companies; to determine the specifics of promoting companies through advertising on the Internet. The research methodology was based on the works on Internet marketing and brand promotion. The authors analysed 5 cases of large Russian companies related to Internet marketing: Aviasales, Yota, Dodo Pizza, Tinkoff Bank, Samokat. In particular, the effective influence marketing of Aviasales and its integration with Yandex were noted alongside with the use of contextual, targeted and unusual advertising by Yota to increase awareness. In addition, the features of managing SMM (social media marketing) by Dodo Pizza, effective advertising campaigns of Tinkoff Bank and commercials based on the research of the target audience of Samokat were highlighted. The following characteristics of brand promotion using online advertising were identified: interactivity, the ability to test advertising creatives, simplicity of calculating results, the need to create bright advertising campaigns in order to increase brand competitiveness.